Assessing non-uniform stiffening of the achilles tendon noninvasively using surface wave. (3rd January 2019) - Salman, Muhammad; Sabra, Karim G.
Abstract: Currently, noninvasive cost-effective techniques capable of quantifying non-uniform degradation of tendon's mechanical and structural properties associated with localized tendon injuries are not readily available. This study demonstrates the applicability of a simple surface-wave elastography (SURF-E) method for assessing the stiffness of the Achilles Tendon by measuring the propagation velocity of surface waves along the tendon in a much broader range of values than currently available Ultrasound-based or MRI-based elastography methods do. Results from this study confirm the non-uniform stiffening of the AT during passive ankle dorsiflexions.